805 Educational programme based on bottom-up learning approach. (8th December 2021) - Spaccarotella, Carmen; Giordano, Salvatore; Esposito, Giovanni; Sinagra, Gianfranco; Indolfi, Ciro
Abstract: A substantial part of the training programme for cardiologists in training includes several hours per week of face-to-face teaching. Since the pandemic's beginning, most of these activities in the universities have been conducted virtually using one of the available secure and reliable video platforms. The proven standard educational method is top-down education. The teacher guides the instruction, focuses on what the students 'need to know', and transmits the knowledge to the fellows, then verifies the learning. Unfortunately, this method does not stimulate critical, creative ability and does not always represent what the fellows 'want to know'. A new additional model of education in the Board of Cardiology of the Magna Graecia University and the University of Trieste has been designed to develop education from the bottom up. The topics that have been chosen are those of the training programme in Cardiology and necessary to complete the training period. A participants list of 60 fellows in training and a panellist list of 3 teachers were then created. The first topic was 'Myocarditis'. Next, each fellow was asked about one topic/question (Figure 1 ) (see additional data). All participants then had to vote for the best five from the pool of 60 questions. Therefore, a pyramid of priorities was made between the topics/questions and assigned to the three panellists, based on specific expertise, 3 days before the event (see additional data). Then a 1, 15 H zoom session was opened at 7:00 AM, and all participants were invited. In the digital session, the fellow authors of the first 15 questions read the question by his/herself, then the moderator entrusted the answer to one of the expert panellists. With this approach, the student started with a question of the selected topic, performs self-directed research or experimentation, and, finally, arrives at explicit knowledge. The general rule of this approach is that participants are the producers and advantages of this method are to teach students how to seek knowledge on their own, even outside the virtual event. In conclusion, this bottom-up educational programme presented can be a valuable teaching aid in the training trajectory of the new generation of physicians.